Determination of JWL parameters from underwater explosion test of spherical explosives by continuous velocity probe. Issue 4 (2nd October 2021) - Li, Kebin; Dong, Xinlong; Li, Xiaojie; Wang, Yonggang; Wang, Wei
ABSTRACT: Underwater explosion test has been proven to be a simple way to measure the equation of state of detonation products. In order to further develop this technology, a new method for determining Jones-Wilkins-Lee equation of state (JWL-EOS) by underwater explosion test with spherical charge was designed based on the self-developed pressure-conducted velocity probe in this paper. First of all, we established an experimental system for the measurement of near-field shock wave of spherical charge using the novel probe, which made it possible to continuously record the velocities of detonation wave and shock wave in a given direction. Four field tests were performed using powdery cyclotrimethylene trinitramine (RDX) and the time history curves of detonation-shock wave front were obtained, by which we determined the velocity of detonation (VoD) and initial shock wave velocity. Besides, the detonation pressure was calculated applying impedance matching technique based on interface continuity conditions and acoustic approximation. We also analyzed the attenuation law of peak pressure of near-field shock wave by fitting the full-scale shock wave data. Applying numerical calculation and test-and-error process, we adjusted the six JWL-EOS parameters ( A, B, C, R 1, R 2, and ω ) constantly to make the error between numerical and experimental attenuation coefficients of peak pressure of shock wave fall within ±1%. Finally, the JWL-EOS parameters of powdery RDX of each test were determined, and the adiabatic curves of pressure versus relative volume were plotted as well.